Association of phenotypic traits and fertility in Holstein heifers: Body condition score, body weight, antral follicle count, anti-Müllerian hormone, and anogenital distance - Andréia Ferreira Machado; Leticia P. Sanglard; Santiago Andres Paez Hurtado; João Victor Chaves; Muhammad Awais Ajmal; José Domingos Guimarães; Jeffrey S. Stevenson; Simone E.F. Guimarães; Victor E. Gomez-Leon (Journal of Dairy Science)
ABSTRACT: The aim of this cross-sectional observational study was to assess whether nulliparous Holstein heifer fertility is associated with (1) energy reserve-related traits, such as BCS and BW; (2) ovarian reserve-related traits, such as anti-Müllerian hormone (AMH) and antral follicle count (AFC); and (3) development-related traits, such as anogenital distance (AGD) and vulval length (VUL). From August 2022 through July 2023, we used a prospective approach in which the phenotypic traits (BCS, AMH, AFC, AGD, BW, and VUL) of 698 Holstein heifers were measured once at approximately 12 mo of age (at the beginning of the breeding program). All heifers were submitted to the herd reproductive management from 367 ± 3 d of age and 297 kg of BW until 570 d of age, or 5 breedings. Fertility outcomes (age at first service, pregnancy per artificial insemination [P/AI] at first service, age at conception, and number of services per conception) were retrieved from software records. Pearson correlations were performed among phenotypic traits collected. The strongest correlations (r >0.5) observed were for AGD with VUL and AMH with AFC. Associations of phenotypic traits with fertility outcomes were determined using generalized linear models. Body condition score was the phenotypic trait most associated with fertility outcomes. Associations of AMH, AFC, AGD, BW, and VUL with fertility were not observed or were very weak. Furthermore, we divided the data into BCS tertiles and performed association analyses by category. The top BCS tertile was associated with greater BW (365.7 ± 1.8 vs. 356.0 ± 1.5 kg), greater P/AI at first service (65.0% ± 4.0% vs. 52.0% ± 4.0%), and fewer number of services per conception (1.5 ± 0.10 vs. 1.8 ± 0.09) compared with the bottom tertile. Moreover, AGD was greater in the top and bottom tertiles compared with the middle tertile. Finally, BCS was associated with time to conception based on the Cox proportional hazards survival analysis, indicating that heifers with greater BCS became pregnant earlier. Based on the results observed in the current study, we would expect benefits for fertility by improving management practices that result in heifers with greater BCS at first service, but ovarian reserve-related traits (AMH, AFC) and developmental traits (AGD, VUL) were not associated with fertility outcomes in our study.